Instrumental role of audit in the area of stock management in the cement industry company - Łęgowik-Świącik, Sylwia; Łęgowik-Małolepsza, Małgorzata; Kowalska, Sylwia (Research Papers of Wrocław University of Economics, 2018)
In the paper, there is discussed the problem of the use of audit in the company, indicating its impact on the efficiency of intermediate product inventory management. The first part of the paper emphasizes the definitions and identification of internal audit in the company. The second part of the paper is the response to the research question. The objective of the paper is to learn and assess the possibilities of using audit for inventory management in the cement industry company in Poland. The conclusions of the research suggest that the implementation of audit determines the efficiency of intermediate product inventory management in the surveyed cement industry company. Research methods applied to accomplish the objective are literature studies and case study
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 52-62
Keywords: audit; inventory management; cement industry; zarządzanie zapasami; przemysł cementowy